URGENSI REGULASI PENYELESAIAN KONFLIK UMAT BERAGAMA: Perspektif Tokoh Lintas Agama - M. Arja Imroni, Abu Hapsin, Komarudin, (WALISONGO, 2014)
This study aimed to determine the attitudes and views of interfaith leaders to theexistence of regulations related to issues of religious harmony in Indonesia. Does theregulation have significant benefits for a variety of efforts to resolve religious conflictsin Indonesia, or precisely the opposite. Locating the research in in Central Java , thisstudy used a qualitative approach. The data is taken from the idea or notion ofinterfaith leaders in Semarang as well as a variety of references related to the centraltheme of research. The data collection extracted by means of interviews and study ofdocuments/ literature. Then, the data were analyzed critical descriptively. The resultsshowed that the religious conflicts that occur due to various factors or root causes ofthe conflict are very diverse. Each of these religious leaders has a different view. Somepeople regarded pluralism as the root causes of conflict, there is also an opinion thatthe cause of the conflict is the existence of discrimination contained in the formulationof laws and regulations are regulated. Despite their differing views on the root causesof the conflict issue, they agreed that in order to maintain religious harmony inIndonesia there needs to be a regulatory laws governing religious life in Indonesia.***Penelitian ini bertujuan untuk mengetahui sikap dan pandangan tokoh lintas agamadengan keberadaan peraturan yang terkait dengan isu-isu kerukunan umatberagama di Indonesia, apakah peraturan tersebut memiliki manfaat yang signifikanbagi upaya penyelesaian konflik agama di Indonesia, atau sebaliknya. Penelitian inidilaksanakan di Jawa Tengah dengan menggunakan pendekatan kualitatif. Datatersebut diambil dari ide (gagasan) tokoh lintas agama di Semarang serta berbagai referensiyang terkait. Pengumpulan data diambil dengan wawancara dan studiliteratur. Data dianalisis secara deskriptif kritis. Hasil penelitian menunjukkan bahwakonflik agama yang terjadi karena berbagai faktor atau akar penyebab konflik sangatberagam. Masing-masing tokoh agama memiliki pandangan berbeda. Beberapaorang menganggap pluralisme sebagai akar penyebab konflik, ada juga pendapatbahwa penyebab konflik adalah adanya diskriminasi dalam perumusan undangundangdan peraturan yang diatur. Meskipun pandangan mereka berbeda pada akarpenyebab masalah konflik, mereka sepakat bahwa untuk menjaga kerukunanberagama di Indonesia perlu ada sebuah hukum yang mengatur peraturan kehidupanberagama di Indonesia.Keywords: keragaman agama, kerukunan beragama, konflik agama,peraturan